Green Education and Digital Transformation as Catalysts for Growth in Iraq: An Economic Analysis of Available Opportunities - Prof. Dr. Nadia Mahdi Abdul Kader (Indonesian Journal of Law and Economics Review, 2026)
General Background Sustainable economic growth requires the integration of environmental sustainability and digital innovation. Specific Background Iraq’s economy is characterized by oil dependence, limited diversification, and underdeveloped education and digital systems. Knowledge Gap Limited studies have examined the combined role of green education and digital transformation in addressing these structural challenges. Aims This study analyzes their joint role in supporting sustainable economic growth in Iraq. Results Green education develops environmentally skilled human capital and supports green sector innovation, while digital transformation improves efficiency, productivity, and market access. Their integration promotes economic diversification, reduces oil reliance, and aligns with Iraq Vision 2030, although constrained by weak infrastructure and limited investment. Novelty The study offers an integrated framework linking green education and digital transformation as complementary drivers of structural reform. Implications The findings highlight the need for coordinated policies, increased digital investment, and stronger international collaboration to support a sustainable and diversified economy. Highlights:• Integration of Environmental Learning and Technology Fosters Diversification Beyond Oil Sectors• Infrastructure Gaps and Limited Funding Constrain Progress in Education and Digital Systems• Policy Coordination and International Collaboration Support Transition Toward Sustainability Keywords: Green Education, Digital Transformation, Sustainable Economic Growth, Iraq Economy, Economic Diversification.